Dealing with Aging Process Facilities and Infrastructure. - Safety), CCPS (Center for Chemical Process (American Institute of Chemical Engineers, 2018)
This concept book explores the many ways in which process facilities, equipment and infrastructure might deteriorate upon continuous exposure to operating and climatic conditions.